DECONSTRUCTION OF MORAL MEANING AND VALUE IN THE POEMS OF "CHAIRIL ANWAR": A HERMENEUTIC REVIEW - Ni Made Erna Artini; I Made Suarta; Ni Nyoman Karmini (SOSIOEDUKASI, 2026)
Poetry is a literary work characterized by symbolic language and layered meanings that require interpretive understanding. Chairil Anwar’s poems have long attracted scholarly attention because of their dense imagery, existential themes, and openness to multiple interpretations. This study aims to reinterpret the meanings embedded in selected poems by Chairil Anwar and identify the moral values they convey through a hermeneutic perspective. A qualitative library research design was employed, using six purposively selected poems: *Aku*, *Doa*, *Derai-Derai Cemara*, *Senja di Pelabuhan Kecil*, *Diponegoro*, and *Krawang-Bekasi*. Data were analyzed through close reading, data reduction, thematic categorization, hermeneutic interpretation, and conclusion drawing. The findings demonstrate that the meanings of these poems are not fixed but are continuously reconstructed through the interaction between the text, its socio-historical context, and the reader’s horizon of understanding. Rather than representing individual expression alone, *Aku* is reinterpreted as an affirmation of existential resilience, *Doa* as a dialogue between human limitation and divine transcendence, *Derai-Derai Cemara* as a reflection on maturity and acceptance of mortality, *Senja di Pelabuhan Kecil* as an exploration of emotional loss and existential solitude, *Diponegoro* as a symbol of collective resistance and national identity, and *Krawang-Bekasi* as a moral reminder of sacrifice and historical responsibility. These reinterpretations reveal enduring moral values, including courage, perseverance, sincerity, faith, responsibility, patriotism, and social solidarity. This study concludes that hermeneutic interpretation enriches the understanding of Chairil Anwar’s poetry by demonstrating how literary meaning evolves across historical and contemporary contexts while preserving its ethical significance.